The Missing State in Postwar American Political Thought - King, D; Stears, M (Oxford University Press, 2009)
“The Missing State in Postwar American Political Thought” (with Marc Stears) in The Unsustainable American State. Eds. Lawrence Jacobs and Desmond King New York: Oxford University Press, 2009.